2012
DOI: 10.1007/s12550-012-0123-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of type A, B and D trichothecenes in barley and barley products from the Bavarian market

Abstract: Fifty-nine samples of barley and barley products were analysed for 18 trichothecene mycotoxins by a sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method (detection limits 0.062-0.70 μg/kg) after sample extract clean-up on MycoSep®-226 columns. The samples were collected in 2009 from barley processing facilities (mills and malt houses) and at wholesale and retail stage from the Bavarian market. The predominant toxins were T-2 toxin (T-2), HT-2 toxin (HT-2) and deoxynivalenol (DON). For all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[7][8][9][10] It has in fact been reported that such mycotoxins as trichothecenes, OTA, and FMs were transferred to commercial beer. [11][12][13][14][15][16] Studies have also been carried out on the fate of such specific mycotoxins as AFB 1 , DON, HT-2, OTA, FMB 1 , and ZON during beer brewing. [17][18][19][20][21][22][23] Despite the fact that many mycotoxins can contaminate the beer or raw materials used in beer manufacture, not all have yet been comprehensively studied.…”
Section: ) Other Significant Mycotoxins Include Trichothecenes (Deoxymentioning
confidence: 99%
“…[7][8][9][10] It has in fact been reported that such mycotoxins as trichothecenes, OTA, and FMs were transferred to commercial beer. [11][12][13][14][15][16] Studies have also been carried out on the fate of such specific mycotoxins as AFB 1 , DON, HT-2, OTA, FMB 1 , and ZON during beer brewing. [17][18][19][20][21][22][23] Despite the fact that many mycotoxins can contaminate the beer or raw materials used in beer manufacture, not all have yet been comprehensively studied.…”
Section: ) Other Significant Mycotoxins Include Trichothecenes (Deoxymentioning
confidence: 99%
“…Barthel et al [144] analyzed fifty nine samples of barley and barley products for 18 trichothecene mycotoxins by a sensitive LC-MS/MS. After sample extract clean-up on MycoSep ® -226 columns, these authors confirmed that LODs were ranged between 0.062-0.70 μg/kg.…”
Section: Current Methods Used For Lc-ms/ms Determination Of Mycotoxins In Cereals Andmentioning
confidence: 99%
“…Of the 30 published LC-MS methods covering the years 2008-2013 that have been reviewed recently [79], ten of them use at least one commercially labelled standard for correction of the analytical results [80][81][82][83][84][85][86][87][88][89]. More recent methods follow this trend and perform SIDAs for all or at least some analysed mycotoxins (Table 1).…”
Section: Commercially Available Labelled Standards For Mycotoxinsmentioning
confidence: 99%